Impact of supercritical pressure on flow heat transfer characteristics and thermal cracking conversion characteristics of n-undecane - Kai Deng (299054) (2025)
This systematic study investigates the flow, heat transfer, and thermal cracking behavior of n-undecane fuel under supercritical pressures, emphasizing the impact of pressure on the dynamics of fuel heat transfer and the kinetics of thermal cracking. Integrating insights from supercritical fluid research – such as the role of local specific heat capacity in heat transfer and pressure effects on microchannel flow – experiments quantify heat absorption, cracking conversion, and product distribution at 2.5–4.5 MPa. Results show that pressure negligibly affects physical heat absorption but modulates chemical heat absorption via pressure-dependent reaction pathways. At fixed conditions (outlet temperature: 650°C; flow rate: 40 mL/min), increasing pressure from 2.5 to 4.5 MPa enhances cracking conversion by 2.55% and gas production by 2.33%. Elevated pressure (3.5→4.5 MPa) promotes the formation of higher-molecular-weight liquid fractions and alkane-dominated gases, suppresses cracking acceleration, and enhances radical reactions (e.g. hydrogen transfer, cyclization). At 620°C, increasing the pressure to 4.5 MPa enhances the heat release of gaseous products, which is attributed to higher gas yields. These findings establish pressure as a critical parameter for optimizing the thermochemical balance between heat transfer and cracking in hydrocarbon fuel systems.